Myofunctional Trainer versus Twin Block in Developing Class II Division I Malocclusion: A Randomized Comparative Clinical Trial - Yasmine Elhamouly; Azza A. El-Housseiny; Hanan A. Ismail; Laila M. El Habashy (Dentistry Journal, 2020)
This study aimed to evaluate and compare the dentoalveolar effects of the myofunctional trainer T4KTM versus twin block in children with class II division I malocclusion. Two parallel arm randomized comparative clinical trial was conducted, including twenty healthy children, 9–12 years old, showing Angle’s class II division I malocclusion due to mandibular retrusion. Children were randomly assigned into two groups according to the appliance used; Group 1: T4k, and Group II: twin block. Follow-up was done every 4 weeks for 9 months. Postoperative cephalometric X ray, study casts and photographs were taken for measurements and comparison. T4K showed a statistically significant reduction in the overjet (−2.50 ± 1.00 mm) (p < 0.0001), and a significant increase in the lower arch perimeter (LAP) (1.19 ± 0.96 mm) (p = 0.01). The twin block showed a statistically significant reduction in the overjet (−3.75 ± 1.10 mm) (p < 0.0001), a significant reduction in the overbite (−16.22 ± 17.02 %) (p = 0.03), and a significant increase in the LAP (1.69 ± 0.70 mm) (p < 0.0001). The overjet showed a higher significant decrease in the twin block group than in T4K (p = 0.03). The mean values of the overbite were significantly decreased in twin block than in T4k (p < 0.0001). Both groups showed significant dentoalveolar improvements toward class I occlusion; however, the twin block showed significantly better results than T4K appliance.